1996
DOI: 10.1177/107769909607300205
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Public Ownership and Newspaper Competition on the Financial Performance of Newspaper Corporations: A Replication and Extension

Abstract: This study supports the conclusions of a 1993 study by Blankenburg and Ozanich that the degree of public ownership affects the financial performance of media groups. High levels of stock ownership outside the media group result in increased returns to stockholders. The current study included competition as an independent variable and found that groups had lower operating margins and spent a greater percentage of revenues on expenses when a higher percentage of newspapers faced newspaper competition. Overall, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Blankenburg and Ozanich (1993) revealed that public ownership and outside control led to short-term financial aims and emphasis on higher return on equity and earning than found in privately owned papers. These findings were later supported by Lacy, Shaver, and St. Cyr (1996), Chang and Zeldes (2002), and Lacy and Blanchard (2003). In contrast to those results, An Jin and Simon (2006) found that institutional ownership is negatively correlated to the subsequent year's profitability.…”
Section: Publicly Traded Ownershipmentioning
confidence: 64%
“…Blankenburg and Ozanich (1993) revealed that public ownership and outside control led to short-term financial aims and emphasis on higher return on equity and earning than found in privately owned papers. These findings were later supported by Lacy, Shaver, and St. Cyr (1996), Chang and Zeldes (2002), and Lacy and Blanchard (2003). In contrast to those results, An Jin and Simon (2006) found that institutional ownership is negatively correlated to the subsequent year's profitability.…”
Section: Publicly Traded Ownershipmentioning
confidence: 64%
“…Porter (1992) reported that the short-term focus of institutional investors was a systemic problem affecting the entire U.S. economy. They found that public companies that had greater inside control were less likely to be influenced by the stock market or pursue short-term returns, a finding affirmed by Lacy, Shaver, and St. Cyr (1996). They found that public companies that had greater inside control were less likely to be influenced by the stock market or pursue short-term returns, a finding affirmed by Lacy, Shaver, and St. Cyr (1996).…”
Section: Background and Literature Reviewmentioning
confidence: 94%
“…Although research suggests that larger newspapers and publicly owned newspapers are more profitable (Blankenburg, 1989;Blankenburg & Ozanich, 1993;Demers, 1996a;Lacy, Shaver, & St. Cyr, 1996;Tharp & Stanley, 1992), my research shows that larger newspapers and publicly owned newspapers (e.g., corporate newspapers) actually place less, not more, emphasis than smaller newspapers on profits as an organizational goal (Demers, 1991(Demers, , 1996a(Demers, , 1996b. In contrast, some research on chain newspapers suggests that they place more emphasis on profits than independently owned newspapers (Busterna, 1988b(Busterna, , 1989Demers: 1991;Demers & Wackman, 1988;McGrath & Gaziano, 1986: Soloski, 1979, but other studies are mixed or suggest that there is no difference between chains and independents (Coulson, 1994;Demers, 1996bDemers, , 1996cOlien, & Tichenor, 1989;Olien, Tichenor, & Donohue, 1988; for review, see Jeffres, 1994).…”
Section: Empirical Researchmentioning
confidence: 95%